Turning Mental Health into Social Action. - Guerin, Bernard (Oxford : Taylor & Francis Group, 2020)
This book deconstructs modern talking therapies, and frames mental health in a wider social context to show how societal structures restrict our opportunities. It is part of a trilogy which offers a new way of doing psychology focusing on people's social environments as determining their behaviour, rather than internal attributions.
6 How can we change language use and thinking in 'mental health'? -- Some points about thoughts in modern Western therapy -- Other interventions for 'mental health' issues involving talking and thinking -- Prayers and praying -- The social contexts for praying, chanting, and recitation -- Music -- Some examples and quotes -- References -- 7 How can we change behaviours shaped by the bad situations produced by societal structures of modernity? -- Bad life problems with hidden bad situations but not considered 'mental health' issues -- Bad life problems with hidden bad situations that are not considered to be 'mental health' issues -- Bad life problems with hidden bad societal situations -- The life conditions produced by modernity -- Effects of capitalism and how to help individuals and groups survive -- Effects of bureaucracy and neoliberalism and how to help individuals and groups survive -- References -- 8 Interventions for 'mental health' symptoms produced by colonization and patriarchal bad situations -- Indigenous approaches: colonization and its aftermath -- What were the bad situations for Indigenous peoples created by colonization? -- What behaviours arise from these bad colonization situations and how might we change them? -- Indigenous interventions -- Feminist approaches: fixing the bad societal situations of women -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Psychology-Social aspects; Electronic books